Effect of Vitamin D on Arterial Stiffness in People with Type 2 Diabetes and Intermediate Chronic Kidney Disease - Rehan Anwar, Muhammad Ahsan Naseer Khan, Nadeem Ahmad Bajwa, Latif Najmi, Shafaq Rafiq, Osama Ali Alamir (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The aim of this study was to investigate the effect of vitamin D therapy on arterial stiffness on diabetic type 2 with intermediate chronic kidney diseases patients. Study design: This was a cross sectional study conducted at Sialkot Medical College, Sialkot for six months from September 2022 to February 2023. Methods: There were 160 participants in total included both male and female gender. The age range was 40-75 years, but majority participants included male 90%. The pulse wave velocity (PWV), 2000 wave unit was measured the arterial stiffness. In an approved laboratory, biochemical parameters such vitamin D, FGF-23, iPTH were assessed by enzyme linked immunoassay, and chemiluminescence immunoassay. Results: A total of 160 participants who were randomly assigned to receive either a placebo (n = 60) or vitamin D (n = 100) were qualified for analysis. The eGFR, serum calcium, phosphate, HbA1c, total cholesterol level, and albumin excretion in both groups did not change significantly throughout therapy; p>0.005. Vitamin D deficiency was significantly increase, p <0.001** in participants, then increased aortic-PWV in the vitamin D therapy group compared to the placebo group. Ao-PWV did not change significantly at the end of the treatment, P>0.005. There is no significant impact of vitamin D on arterial stiffness. Conclusion: In T2DM with moderate CDK, the aortic-PWV, augmentation index, and pressure measurements of arterial stiffness were all substantially higher in the vitamin D deficient group compared to the vitamin D sufficient group. Keywords: Chronic kidney disorder, Diabetes type 2, Pulse wave velocity, Aortic.